Music teachers' perceptions of teaching multicultural music in Malaysia - Wong, K.Y.; Chiu, M.Y. (2016)
The purpose of this study was to investigate the perceptions of the music teachers associated to the teaching of multicultural music education in Malaysian primary schools. The data were collected through semi-structured interviews. The findings that were examined in this paper address the following research questions: l)What are the perceptions of music teachers regarding multicultural music education provided by their teacher training programs? 2) What aspects of teaching multicultural music education do music teachers perceive as most challenging? 3) What teaching approaches and activities are the most appropriate for multicultural music in the primary music classes? The findings revealed that music teachers reported that they did not have adequate multicultural training during their college courses. Besides, there is limited implementation of multicultural music education in music classrooms due to that many music teachers do not possess appropriate multicultural music knowledge and resources to teach multicultural music. Music teachers also reported that the activities and approaches used in class must involve the students actively, rather than passively receptive and also need to allow them to obtain first-hand experience of playing the traditional musical instruments. Therefore, music teacher training programmes are needed in order to address both the theoretical and practical aspects of multicultural music education throughout the curriculum in a comprehensive and long-term manner. Implications for multicultural music teaching and research were discussed in this paper.